Studi Karakteristik Infiltrasi dan Limpasan Aliran terhadap Waktu dengan Tutupan Lahan Rumput Jenis Zoycia Japonica - Alvin Lauw; Robby Yussac Tallar (Journal of Smart Technology and Engineering, 2025)
Indonesia, which is known as a country with a tropical climate and is traversed by the equator, causes the country to have quite high rainfall. Flood problems often occur in Indonesia, especially in big cities, including the capital city or the city of Jakarta, which is one of the cities that is often hit by floods. The purpose of this experiment is to see whether the vegetation on the soil affects the coefficient C of the runoff and flow rate that occurs. Zoycia Japonica grass species has adequate infiltration capacity. The first scenario is that the infiltration results obtained from the practicum are not much different from the calculation results without grass or soil media. The results of the calculation have results for the first minute 6.67 ml, the second minute 13.3 ml, the third minute 20 ml, the fourth minute 26.67 ml, the fifth minute 33.37 ml. As for the results of the first scenario practicum, the results for the first minute were 6.3 ml, the second minute 12.88 ml, the third minute 19.87 ml, the fourth minute 26.33 ml, the fifth minute 32.99 ml. For the first scenario, the value of the coefficient C also has a value of 0 which means that no rainwater will run off on the surface. For scenario 2, zoycia grass also still shows a good coefficient C, which can be seen from the total runoff discharge, which is only around 4.16 ml/minute and has a coefficient C value of 0.6933. Keywords: Zoycia Japonica Grass, Runoff Coefficient C Value, Infiltration